Nationalism Education at the Lirboyo Islamic Boarding School, Kediri - Nur Khozin; A. Jauhar Fuad (Jurnal Pendidikan Islam Indonesia, 2022)
This paper answers about nationalism education at the Lirboyo Islamic boarding school. This paper uses an ethnomethodological method. The results of the research, namely: first, Nationalism Education does not only focus on education in the classroom, even outside the classroom. This can be seen from several aspects. Both from the social environment, culture, state symbols and also in every process of Pondok Pesantren activities. Second, the task of the teacher must be able to provide an example of nationalism and tenacity in educating the students. Therefore, a teacher must have standardization, terms and criteria in teaching nationalism education. Third, the Lirboyo Islamic Boarding School made a nationalism curriculum that was taught to students at the Ma'had Aly level which was contained in the National Fiqh book..